Tantangan Menyelenggarakan Pendidikan Islam Di Panti Asuhan - Ayu Tegar; M. Rohman Wahono (STIT Muhammadiyah Bangil Pasuruan, 2025)
This research aims to examine the challenges of implementing Islamic education at the Aisyiyah Ponorogo Integrated Blind Orphanage. This research uses a qualitative approach with a descriptive type. Data collection was obtained through interviews with education administrators and two blind students at the Aisyiyah Ponorogo Integrated Blind Orphanage. This research shows that there are two types of challenges to Islamic education at the Aisyiyah Ponorogo Integrated Home for the Blind, namely, challenges to infrastructure and inclusive learning methods. In terms of infrastructure, new iqras are not available and there is a lack of classrooms for carrying out learning. The teacher's inability to read and write Arabic braille and how to teach blind students also influences the learning process at the orphanage.